In-situ horizontal cyclic loading tests on composite foundation composed of soilbags and piles - Tatsuya Doi; Yoshitaka Murono; Feng Zhang; Yuji Hirayama (Soils and Foundations, 2023)
The authors have been developing a new composite foundation composed of piles and soilbags. The foundation is characterized by the laying of soilbags between the pile heads and the footing on which a superstructure stands. The expected effect of the foundation is to cut off the fixed connection between the piles and the footing in order to reduce the bending moment of the piles and the response acceleration of the structure. In this study, in-situ horizontal cyclic loading tests were conducted on the proposed composite foundation with two piles to investigate the seismic response characteristics of the foundation at real scale. It was found from the tests that the horizontal force reached its peak due to the uplift of the footing during horizontal loading, and that larger hysteresis damping was obtained than that of spread foundations due to the hysteresis effect in the shear deformation of the soilbags. As for the sectional force of the piles and the vertical stress inside the soilbags, it was found that the axial force and bending moment of the piles concentrated on the pile on the front side in the loading direction, and that the vertical stresses inside the soilbags concentrated just above the pile head on the front side in the loading direction. Although residual horizontal displacement and settlement occurred due to the cyclic load, little damage to the soilbags was observed.